Exploitation of job's tears in Paleolithic and Neolithic China: Methodological problems and solutions. (20th September 2019) - Liu, Li; Duncan, Neil A.; Chen, Xingcan; Cui, Jianxin
Abstract: Job's tears ( Coix lacryma-jobi ) is believed to be native to tropical and subtropical regions of Asia, and has been used as food widely throughout Asia since prehistory. In China, this cereal is frequently mentioned in ancient texts as being used in food, medicine, and alcoholic beverages. It also assumed significance in dynastic legends. However, unlike other cereals, Job's tears' dispersal and domestication process remain unclear. The macrofossil remains of this plant have only been found sporadically at about seven sites from the Neolithic to the Han dynasty (ca. 7000-1800 cal BP); but its microfossil remains have been recovered from more than 30 sites across China, ranging from tropical to temperate zones, and dating to as early as 28, 000 cal. BP. This discrepancy between macrofossil and microfossil findings poses a challenge to archaeobotanists. This paper presents a multi-disciplinary approach to investigate the depositional processes of Job's tears in archaeological contexts, including ethnographic observation, starch and phytolith analyses, use-wear analysis of stone tools, and experimental charring. We propose methods for identifying its microfossil remains, which may help to explore the possible pathways of its domestication in the future. Based on current archaeological data, Job's tears was already collected as a starchy food source by Upper Paleolithic populations in China by 28, 000 cal BP, but it may have largely disappeared during the cold and dry episode of Younger Dryas in a large part of north China. While this plant appears to have been exploited during the early Holocene in the Huai and Yangzi river regions, no evidence indicates its presence in the temperate zones north of the Yellow river until after 8000 cal. BP. The reasons for such changes still need to be investigated. However, it is noted that Job's tears became widespread in the Neolithic period, coinciding in time and space with the development of millet domestication over a broad region in the Yellow River and Liao River valleys. This plant may have been a component of farming practices during the mid-Holocene climatic maximum in China, but more comprehensive analyses need to be done to investigate its domestication process.